Kampung Tangguh Bencana Era Digital Akselerasi Ekonomi dan Layanan Sosial Berbasis Teknologi - Nayra, Nayra; Sunarto, Dede Joko; Tiananda, Nathania; Rahmania, Silvi (Prima Abdika: Jurnal Pengabdian Masyarakat, 2025)
Digital transformation has become an urgent necessity for promoting economic independence and improving social service efficiency in Kampung Tangguh communities. However, most Micro, Small, and Medium Enterprises (MSMEs) in Kampung Tangguh RW 27, Siantan Hulu Subdistrict, Pontianak City, lack digital business identity and presence on digital platforms, while integrated service posts still use manual recording systems. This community service program employed a Community Development (CD) approach with active community participation. The program was implemented over one month (July 7-31, 2025) and focused on three main interventions: MSME digitalization through social media training and digital branding, digitalization of integrated service post recording systems using Google Sheets, and development of community digital identity through official social media accounts. Three out of six targeted MSMEs participated in content creation training using CapCut and social media management on Instagram and TikTok. One MSME completed a rebranding with a new logo design. The integrated service post successfully transitioned from manual recording to digital spreadsheet format covering five categories: post profile, child development data, school age and adolescent data, adult data, and elderly data. Official Instagram and TikTok accounts were created for community information sharing and local product promotion.  The gradual, contextual, and humanistic digitalization approach effectively increased community awareness and readiness to utilize technology. Despite not all partners being fully involved, positive impacts were observed among active MSMEs, integrated service post cadres, and village residents. This transformation provides an important foundation for larger and more sustainable program development in local economic improvement and social service efficiency.